2008
DOI: 10.1007/s00408-008-9128-0
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic and Anaerobic Exercise Capacities in Obstructive Sleep Apnea and Associations with Subcutaneous Fat Distributions

Abstract: Obesity is a strong risk factor for the development and progression of sleep apnea. Responses to exercise by patients with obstructive sleep apnea syndrome (OSAS) are clinically relevant to reducing body weight and cardiovascular risk factors. This study aimed to clarify the aerobic and anaerobic exercise capacities and their possible relationships with other findings in patients with OSAS. Forty patients (30 males, 10 females) and 40 controls (30 males, 10 females) were enrolled in this study. Questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 28 publications
4
39
0
Order By: Relevance
“…[8][9][10] The impact of OSA on exercise capacity remains unclear. Prior studies examining exercise capacity in OSA patients have yielded confl icting results, with some demonstrating reduced exercise capacity [11][12][13][14][15][16] and others suggesting exercise capacity is not impaired. [8][9][10]17,18 These studies have several methodological limitations that make reconciling their fi ndings challenging.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] The impact of OSA on exercise capacity remains unclear. Prior studies examining exercise capacity in OSA patients have yielded confl icting results, with some demonstrating reduced exercise capacity [11][12][13][14][15][16] and others suggesting exercise capacity is not impaired. [8][9][10]17,18 These studies have several methodological limitations that make reconciling their fi ndings challenging.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…After adjusting for baseline differences, this association remained signifi cant (p < 0.01). AHI alone explained 16.1% of the variability observed in percent predicted peak O 2 (p = 0.02). Conclusions: OSA is associated with impaired exercise capacity.…”
mentioning
confidence: 96%
“…However, these results conflict with many other reports that have described higher maximal V'O2 in non-OSA than in 6,22). Reinforcing this last observation, some studies have shown that AHI is inversely correlated with peak V'O2 during CPET (3,5,22,23). Nevertheless, other factors have also been implicated in the exercise capacity of patients with OSA, such as age, BMI, body weight and sex (2,10,22-24).…”
Section: Correlations Between Sleep Register and Cardiopulmonary Exermentioning
confidence: 85%
“…Ucok et al (27) found that aerobic capacity was significantly lower in OSAS patients than in controls. These findings in the literature mentioned above (25)(26)(27) might be interpreted that the aerobic capacity was lower and the anaerobic metabolism was more developed in the patients with OSAS than normal subjects. Lactic acid, a product of anaerobic metabolism, largely is broken down with using O 2 during non rapid muscle activity.…”
Section: Discussionmentioning
confidence: 96%